2013
DOI: 10.3390/ijms141122449
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Comet Assay for Assessing the Dose-Response Relationship of DNA Damage Induced by Ionizing Radiation

Abstract: Dose- and time-response curves were combined to assess the potential of the comet assay in radiation biodosimetry. The neutral comet assay was used to detect DNA double-strand breaks in lymphocytes caused by γ-ray irradiation. A clear dose-response relationship with DNA double-strand breaks using the comet assay was found at different times after irradiation (p < 0.001). A time-response relationship was also found within 72 h after irradiation (p < 0.001). The curves for DNA double-strand breaks and DNA repair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 28 publications
1
23
1
3
Order By: Relevance
“…The dose-dependent increases in DNA damage, expressed as OTM values, are shown immediately after irradiation of up to 8 Gy at the LDR (3.6 Gy/min) and HDR (36 Gy/min). The range of OTM values at 0 h corresponded with the data reported in the literature for the similar doses of irradiation [ 16 ]. After 24 h of LDR irradiation, the levels of DNA breaks in K562 cells were significantly lower than immediately after exposure and did not differ from the corresponding control.…”
Section: Resultssupporting
confidence: 84%
“…The dose-dependent increases in DNA damage, expressed as OTM values, are shown immediately after irradiation of up to 8 Gy at the LDR (3.6 Gy/min) and HDR (36 Gy/min). The range of OTM values at 0 h corresponded with the data reported in the literature for the similar doses of irradiation [ 16 ]. After 24 h of LDR irradiation, the levels of DNA breaks in K562 cells were significantly lower than immediately after exposure and did not differ from the corresponding control.…”
Section: Resultssupporting
confidence: 84%
“…Related to this, it is still unknown how quickly a Cas9-induced break is repaired. DSBs have been measured by comet assays ( Wang et al., 2013 ) or pulsed-field gel electrophoresis, typically ( DiBiase et al., 2000 ) after exposure to high doses of ionizing radiation that cause hundreds of DSBs per cell. Time courses of such bulk measurements in mammalian cells have consistently shown that DSBs are generally repaired with a half-life of 10–60 min ( DiBiase et al., 2000 , Metzger and Iliakis, 1991 , Núñez et al., 1995 , Schwartz et al., 1988 , Stenerlöw et al., 2003 , Wang et al., 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…The comet assay is a single‐cell gel electrophoresis assay that assesses the extent of DNA damage in nucleated white blood cells by applying a computerized scoring algorithm. The extent of DNA damage is estimated from approximately 100 comets per sample analyzed by CASP software (CaspLab, Wroclaw, Poland) and values are expressed as a mean score from 0 to 4 (maximum damage/large tail) …”
Section: Methodsmentioning
confidence: 99%
“…The extent of DNA damage is estimated from approximately 100 comets per Cancer January 15, 2019 sample analyzed by CASP software (CaspLab, Wroclaw, Poland) 52 and values are expressed as a mean score from 0 to 4 (maximum damage/large tail). 53…”
Section: Dna Damagementioning
confidence: 99%